PERSEPSI GURU TERHADAP PENGAWASAN KEPALA SEKOLAH DI SEKOLAH MENENGAH PERTAMA NEGERI I KECAMATAN SASAK RANAH PASISIE KABUPATEN PASAMAN BARAT - Nessa Zilfari (Universitas Negeri Padang, 2013)
The background of this research from the author's observation on Teacher Perceptions Toward Supervision Principal at SMPN 1 Sasak Ranah Pasisie Regency Pasaman Barat not as expected. The purpose of this study was to obtain information about: Teachers Perception on. (1) Aspects of supervised, (2) monitoring techniques, (3) Time and supervision, (4) Follow-up. This research is a descriptive form. Population is all Teachers SMPN 1 Sasak Ranah Pasisie Regency Pasaman Barat which amounts to 42 people. Insrument research using a questionnaire with a Likert scale models of alternative answers provided consists of 5 scales are always (SL), often (SR), Sometimes (KD), rarely (JR), and never (TP). Before the questionnaire was distributed to a data source testing prior to 10 teachers at SMPN 1 Regency Pasaman Barat which does not include the data source to determine the validity and reliability of the questionnaire. Test results are valid and reliable questionnaire. The data were processed using the formula data. The results showed: Teacher Perceptions of the aspects which are supervised on an average score of 3.4 and be in reasonably well. Teacher perceptions of the Control Techniques is the average score of 3.5 and be in good enough qualification. Teacher perceptions of the Time Control is the average score of 3.4 and be in good enough qualification. Teacher perceptions of the Follow-up monitoring is the average score of 3.7 and be in good qualifications. Overall average score of Teacher Perceptions Toward Supervision Principal at SMPN 1 Sasak Ranah Pasisie Regency Pasaman Barat is 3.5 and is in the category Good Enough. Thus the results of the study showed that the Teacher Perceptions Toward Supervision Principal at SMPN 1 Disryct Sasak Ranah Pasisie Regency Pasaman Barat good enough. Kata kunci : Persepsi guru Pengawasan kepala sekolah